Post oblique ballistic impact behaviour of hybrid composite plates reinforced with carbon nanotubes - Randjbaran, Elias (2022)
The present experimental investigation endeavoured to examine the tensile, compression, and 3-point bending strength of the laminates made of carbon/Kevlar hybrid reinforced textiles with carbon nanotubes (CNTs) fillers subjected to oblique ballistic impact loads. The advanced nano-fillers were chosen as reinforcement for the carbon/Kevlar hybrid textile composite because of their high Young's modulus. Although there are a number of experimental investigations on tensile properties of CNTs, the coupling effects of CNTs and oblique impacts on tensile, compression, and 3- point bending strengths have not been examined yet. Consequently, individual oblique impacts ranging from 0 to 40 degrees were conducted on the composite plates made-up of fabrics with diverse volumes of CNTs, which ranged from 0.1% to 1.5%. The plates were fabricated with eight layers of equal thickness arranged in different percentages of CNTs and neat epoxy resin. A conical steel projectile at dimensions of 15 mm length and 10 mm diametre was considered for a high velocity impact. While the projectile was placed very close to the plates, i.e. at their centres, they were impacted at sundry speeds. The modulus of elasticity and toughness were calculated for the stress-strain curves obtained from the mechanical tests. In the progress of the experiments, the variation of the kinetic energy, the increase in the internal energy of the laminates, and the decrease in the velocity of the projectile with disparate angles were examined. Results from the experimental tests indicated that the kinetic energy absorption of the projectile increased by 38% with the increase of the oblique angle of 40 degrees at 0.3% CNTs' desperation. The optimum dispersion of the CNTs fillers was 0.3% and by adding the CNTs, the kinetic energy absorption increased by about 35%. Additionally, the inclusion of the CNTs' fillers by 1.5% resulted in improving the compressive toughness of the specimens more than triple times. The increase of CNTs fillers by 1.5% caused the decrease of the tensile strength and toughness by 86%. Moreover, the incorporation of 1.5% of CNTs caused the increase of the flexural bending toughness of the specimens more than four times. Simultaneously, the flexural modulus of elasticity decreased by up to 38%. The incorporation of CNTs by 1.5% increased the flexural bending toughness more than four times; however, the flexural modulus of elasticity decreased by up to 38%.